(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
While Indian authors – writers, novelists, essayists, dramatists – have been making significant and considerable commitments to world literature since the pre-freedom era, the past couple of years have seen a gigantic prospering and flourishing of Indian English writing in the global market. Indian English literature is a legitimate enterprise to demonstrate the ever rare diamonds of Indian writing in English. Indian English has ended up being another shape of Indian culture and voice in which India banters regularly. Not exclusively are crafted by Indian authors writing in English surging on the blockbuster list, they are also earning an enormous amount of critical acclamation. Initiating from Shashi Pande, the panache of fine Indian writers is long and much augmented. In this paper we will discuss about the opinion of Shashi Deshpande towards Feminism and Social realism in his works.